ChemInform Abstract: An Efficient One‐Pot Organocatalytic Synthesis of 9‐(1H‐Indol‐3‐yl)‐xanthen‐4‐(9H)‐ones under Mild Aqueous Micellar Conditions. Issue 15 (25th March 2013) - Ganguly, Nemai C.; Roy, Sushmita; Mondal, Pallab; Saha, Rajat
Abstract Electron‐rich indoles and N, N‐dimethylaniline are successfully coupled with o‐hydroxybenzaldehydes and dimedone in the presence of L‐proline.